Pengenalan Sistem Penyiraman Otomatis Sebagai Metode Irigasi Pada Tanaman Obat Keluarga (TOGa) - Adi Kusuma, Yudha; Irna Tri Yuniahastuti; Siti Muhimatul Khoiroh (Universitas Mandiri Bina Prestasi (UMBP), 2024)
Technological developments in agriculture are becoming increasingly sophisticated as time goes by. This technology aims to facilitate human work and increase production results. One technology that supports agriculture is automatic watering. A strategic step in realising increased yields in Family Medicinal Plant (TOGa) cultivation can be achieved with the introduction of an automatic watering system. Limited land use in planting TOGa, supported by the use of automatic watering, is expected to be able to become an additional source of income for the community. This service activity was carried out in Purwoseco Hamlet and Karangrejo Hamlet for ± 1 month. Service activities are carried out each week in two sessions. The number of dedication participants was 20. The service phase begins with a location survey, an introduction to the design of the watering technique, tutorials for making watering installations, and an evaluation of activities. The form of evaluation activities is carried out by testing independent statistical t tests on two groups. The perceived results of this service activity are that many participants feel optimistic when the service is finished and will implement an automatic watering system on their respective lands. This refers to the results of statistical tests using an independent t test, which is known to accept Ho as a result of the Sig value of 0.05. In addition, another result of this community service activity is that service participants think that the watering system is automatic.